Shape optimization of a hyperloop pod's head and tail using a multi-resolution morphing method. (1st June 2022) - Kim, Honghee; Oh, Sahuck
Abstract: In the current study, the 3D shape optimization of a hyperloop pod's head and tail is carried out to improve the pod's aerodynamic performance. For shape exploration, a new shape design method called multi-resolution morphing is applied with three baseline hyperloop models, where each has its own aerodynamic characteristics. As a result, an optimal hyperloop pod with a drag value that is 7.5% smaller with respect to the baseline model and optimal pods with well-balanced drag and lift values are obtained. From further investigations, several meaningful results are also discovered. First, the shape of the tail has a greater impact on the drag and lift of the hyperloop pod than the shape of the head, and this difference is more remarkable in the drag than the lift. Second, changing the shape of the head does not elicit a large effect on the aerodynamic performance of the tail and vice versa. Accordingly, the optimization of a hyperloop pod's head and tail can be implemented independently. A high correlation between the strength of the turbulent kinetic energy around the tail and drag is also found from a flow comparison between the optimal models. Finally, the local flow characteristics are similar for the models that are constructed with the same coefficients of the high-degree spherical harmonics. This indicates that it is possible to transfer the local flow characteristics of one model to the other via the multi-resolution morphing method. Graphical abstract: Highlights: The shape optimization of a hyperloop pod is carried out to improve its aerodynamic performance. A new design method called multi-resolution is applied for the various hyperloop pod's shape exploration. Influences of the shapes of the hyperloop pod's head and tail are investigated. The flow characteristics around baseline and optimal hyperloop models are analyzed.